Native American mythology A to Z - Lynch, Patricia Ann. (New York Facts On File, 2004)
Features over four hundred entries that explore such topics as the core beliefs of various tribes, creation accounts, and recurrent themes throughout North American native cultures. The beliefs of many Native American peoples emphasize a close relationship between people and the natural world, including geographical features such as mountains and lakes, and animals such as whales and bison. Therefore, many of the myths of these peoples are stories of strange occurrences where animals or forces of nature and people interact. These stories are full of vitality and have captured the attention of young people, in many cases, for centuries. Native American Mythology A to Z presents detailed coverage of the deities, legendary heroes and heroines, important animals, objects, and places that make up the mythic lore of the many peoples of North America from northern Mexico into the Arctic Circle. A comprehensive reference written for young people and illustrated throughout, this volume brings to life many Native American myths, traditions, and beliefs. Offering an in depth look at various aspects of Native American myths that are often left unexplained in other books on the subject, this book is a valuable tool for anyone interested in learning more about various Native American cultures. Coverage includes creation accounts from many Native American cultures; influences on and development of Native American mythology; the effects of geographic region, environment, and climate on myths; core beliefs of numerous tribes; recurrent themes in myths throughout the continent. The beliefs of many Native American peoples emphasize a close relationship between people and the natural world
Introduction -- Time line of North American cultures -- Map of Native American culture areas -- A-to-Z entries -- Selected bibliography
Includes bibliographical references (p. 122-124) and index
Keywords: Indian mythology -- North America